The association of nonalcoholic fatty liver disease with central and peripheral blood pressure in adolescence. Issue 3 (March 2015) - Patel, Sumaiya; Lawlor, Debbie A.; Ferreira, Diana L.S.; Hughes, Alun D.; Chaturvedi, Nish; Callaway, Mark; Day, Chris; Sattar, Naveed; Fraser, Abigail
<x xml:space="preserve">Abstract</x> Objectives: We aimed to determine the association of nonalcoholic fatty liver disease (NAFLD) with central and peripheral blood pressure (BP), in a general adolescent population and to examine whether associations are independent of adiposity. Methods: Using cross-sectional data from a subsample (N = 1904) of a UK birth cohort, we assessed markers of NAFLD including ultrasound scan (USS) determined fatty liver, shear velocity (marker of liver fibrosis), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma-glutamyltransferase (GGT) at a mean age of 17.8 years. These were related to BP [central and peripheral SBP and DBP and mean arterial pressure (MAP)]. Results: Fatty liver was positively associated with central and peripheral SBP, DBP and MAP in models adjusting for age, sex, social class, puberty and alcohol intake. These positive associations were attenuated to the null when fat mass was included. For example, in confounder-adjusted models, not including fat mass, mean central SBP was 3.74 mmHg [95% confidence interval (CI) 1.12 to 6.36] higher in adolescents with USS fatty liver than in those without; with additional adjustment for fat mass, the association attenuated to the null value (−0.37 mmHg; 95% CI –3.09 to 2.36). Similar patterns were found for associations of ALT and GGT with central and peripheral BP. There was no consistent evidence of associations of shear velocity or AST with BP measurements. Fatty liver was not consistently associated with central pulse pressure (PP), peripheral PP and Aix@75. Conclusion: NAFLD is not associated with higher central or peripheral BP in adolescents once confounding by adiposity is taken into account.